2021
DOI: 10.1177/1753193420981852
|View full text |Cite
|
Sign up to set email alerts
|

A volar approach to on-top plasty for correction of radial polydactyly: a case series of 21 patients

Abstract: Correction of unequal radial polydactyly in which neither thumb duplicates possess both well-developed proximal and distal components, remains challenging. Current techniques using on-top plasty techniques require circumferential incisions, often resulting in postoperative swelling and dorsal scars. We described our experience using a volar approach to achieve better aesthetic and functional results. Twenty-one patients underwent this surgery between 2008 and 2018, with a mean follow-up of 5.1 years. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In cases of unequal polydactyly, neither thumbs are considered dominant and require combining parts of each thumb, such as in the Bilhaut-Cloquet technique; however, this procedure is technically demanding, commonly producing nail bed deformities and an overall poor aesthetic outcome. 9,10 Mak et al 9 improved upon this historical technique with a neurovascular island flap that includes the pulp tissue and nail bed from the resected digit and a dorsal skin flap on the retained digit to improve size and symmetry (Figure 2). Fang et al 10 presented a modified on-top plasty to avoid dorsal scars by using palmar incisions and a pedicled transposition flap for first webspace correction found in unequal polydactyly.…”
Section: Polydactylymentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of unequal polydactyly, neither thumbs are considered dominant and require combining parts of each thumb, such as in the Bilhaut-Cloquet technique; however, this procedure is technically demanding, commonly producing nail bed deformities and an overall poor aesthetic outcome. 9,10 Mak et al 9 improved upon this historical technique with a neurovascular island flap that includes the pulp tissue and nail bed from the resected digit and a dorsal skin flap on the retained digit to improve size and symmetry (Figure 2). Fang et al 10 presented a modified on-top plasty to avoid dorsal scars by using palmar incisions and a pedicled transposition flap for first webspace correction found in unequal polydactyly.…”
Section: Polydactylymentioning
confidence: 99%
“…9,10 Mak et al 9 improved upon this historical technique with a neurovascular island flap that includes the pulp tissue and nail bed from the resected digit and a dorsal skin flap on the retained digit to improve size and symmetry (Figure 2). Fang et al 10 presented a modified on-top plasty to avoid dorsal scars by using palmar incisions and a pedicled transposition flap for first webspace correction found in unequal polydactyly. Where resection and reconstruction of the preserved thumb is indicated, the fillet flap has been the conventional technique used to improve contour of the retained thumb.…”
Section: Polydactylymentioning
confidence: 99%
“…The thumb with the better-developed distal portion is isolated with its neurovascular pedicle and tendons and is transposed onto the proximal portion of the other thumb 44 . Studies of this technique have shown preserved functional range of motion and good quality-of-life scores 52,53 .…”
Section: Treatment and Operative Techniquementioning
confidence: 99%
“…Shortcomings with this technique include issues around swelling, a short thumb, narrow first web and unpleasant dorsal scar formation [16,17]. Fang et al [18 ▪ ] in 2021 presents a volar approach to on-top plasty as an alternative to the traditional circumferential incision that avoids a dorsal scar, while increasing the length of the retained thumb and broadening the first web space. They also suggest meticulous reconstruction of the flexor and extensor tendon to strengthen the power for pinch and grasp and advocate early surgery wherever possible, to allow time for growth and secondary development.…”
Section: Handmentioning
confidence: 99%